North Caucasian Poetry at the Turn of The Centuries: End of the 20th Beginning of the 21st Century / 20. Yüzyıl Sonlarından 21. Yüzyıl Başlarına Kadarki Süreçte Kuzey Kafkasya Şiiri” - Izeta Vladimirovna Mamieva* (Cyprus International University, 2021)
The modern North Caucasian poetry as the phenomenon in the context of the allRussian literary process is investigated in the article, as well as implementation of the concept of an innovative model of poetic understanding of the world and the forms of its representation. The synthesis of artistic discoveries generated by the sensations and views of the 21st century man is specified as its characteristic feature, with the priority of the fundamental values and stereotypes established in the popular consciousness, clearly observed in the minds of both the recognized masters and the younger generation of poets. The ideological and aesthetic principles of the development of reality, the individual and stylistic peculiarities of poetic creativity are highlighted in the article. The analysis of the works of the Balkar, Karachay, Ossetian, Chechen authors enables to introduce into scientific circulation a number of new names; an attempt is made to reproduce a holistic picture of the modern artistic thought of the reviewed region, formed on the basis of the closest interconnections with the ethnonational existence and social cultural dynamics of the Russian society. As a result of the study, key points in the development of the creative consciousness of North Caucasian authors were identified, the aesthetic-semantic hierarchy, ethnocultural sources and dominants of value-orientation unity in the content and problematics of works were indicated. And the structural features of the poetic text, modified in Russian poetry of the 21 century, in a comparative aspect with the modern North Caucasian poetic culture are also examined.